2022
DOI: 10.1590/1414-431x2022e11777
|View full text |Cite
|
Sign up to set email alerts
|

Effects of traction therapy on atlantoaxial joint dislocation-induced cervical vertigo

Abstract: Cervical vertigo is a common complication of atlantoaxial joint dislocation. However, there is no consensus on the effects of different therapies on the recovery of the patients suffering cervical vertigo. The objective of this randomized controlled trial was to investigate the effect of traction therapy on reducing cervical vertigo induced by atlantoaxial joint dislocation. A total of 96 patients were randomized to receive traction therapy or traditional therapy for two weeks. The overall clinical efficacy wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Some studies have suggested that Atlantic Rotary Fixation (AARF) is the main cause of CV. [ 20 ] AARF refers to any deviation from the normal rotation of the atlantoaxial complex in the upper cervical spine due to traumatic or non-traumatic causes. [ 21 ] The treatment of AARF mainly includes conservative manipulation and invasive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that Atlantic Rotary Fixation (AARF) is the main cause of CV. [ 20 ] AARF refers to any deviation from the normal rotation of the atlantoaxial complex in the upper cervical spine due to traumatic or non-traumatic causes. [ 21 ] The treatment of AARF mainly includes conservative manipulation and invasive surgery.…”
Section: Discussionmentioning
confidence: 99%